Multi-Cultural Nature of Modern Projects: Culture as a Critical Success Factor for a Successful Project Management in Multinational IT Service Projects - Nur Allisyah Aiman Norsani,; Balqis Aqila Asha’ari,; Muhammad Luqman Hakim Razlan,; Muhammad Nazri Md Salman,; Muhammad Farris Hirzan Noor Zamrie,; Muhammad Firdaus Ahmad Nazri,; Amirul Hakim Hezri,; Siti Hajar Arbain, (Applied Information Technology And Computer Science, 2023)
In the contemporary global business landscape, this paper investigates the impact of cultural management as a fundamental discipline within project management on the success of globally delivered IT service projects. A qualitative research design, derived from an extensive literature review, explores the critical role of cultural awareness and management in international projects, particularly emphasizing challenges in cross-cultural communication. Interview data is juxtaposed with scholarly literature to validate the findings. The culmination of empirical research and literature insights results in the development of a Project Management Cultural Framework, highlighting culture and communication as core issues in international project teams. The framework underscores the challenges posed to project managers and organizations managing inter-cultural teams, offering valuable insights for building successful project teams in a global context.